2021
DOI: 10.1038/s42003-021-01820-z
|View full text |Cite
|
Sign up to set email alerts
|

The gut mycobiome of healthy mice is shaped by the environment and correlates with metabolic outcomes in response to diet

Abstract: As an active interface between the host and their diet, the gut microbiota influences host metabolic adaptation; however, the contributions of fungi have been overlooked. Here, we investigate whether variations in gut mycobiome abundance and composition correlate with key features of host metabolism. We obtained animals from four commercial sources in parallel to test if differing starting mycobiomes can shape host adaptation in response to processed diets. We show that the gut mycobiome of healthy mice is sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 53 publications
(74 reference statements)
1
51
0
Order By: Relevance
“…The fungal numbers in the three sample groups were comparable; however, protein levels in Acremonium, Wickerhamomyces, Rhodotorula, and Rhizopus were substantially higher in the persisted group than in the outgrown and healthy groups (p < 0.05). This result suggested that fungi were not only present but also metabolically active in the guts of infants, emphasizing the link between gut mycobiome and host health [59,60].…”
Section: Discussionmentioning
confidence: 86%
“…The fungal numbers in the three sample groups were comparable; however, protein levels in Acremonium, Wickerhamomyces, Rhodotorula, and Rhizopus were substantially higher in the persisted group than in the outgrown and healthy groups (p < 0.05). This result suggested that fungi were not only present but also metabolically active in the guts of infants, emphasizing the link between gut mycobiome and host health [59,60].…”
Section: Discussionmentioning
confidence: 86%
“…Although the proportion of fungi in gut microbiota is low, it is closely associated with the feeding, immunity, and metabolic health of the host (6)(7)(8). Studies on the relationship between gut fungi and host health have confirmed that an imbalance in the gut fungal flora can cause diarrhea (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…However, as indispensable members in gut microbial communities, gut fungi and their roles in the occurrence and development of obesity are little investigated 10,11 . Recently, Tahliyah's study showed the genera Thermomyces and Saccharomyces most strongly associate with metabolic disturbance and weight gain 12 . And Borges reported a mycobiota shift towards obesity, the increased yeast in obese human individuals, and more filamentous fungi in the eutrophic human individuals 13 .…”
mentioning
confidence: 99%